PENGARUH BUKU SAKU BILINGUAL TERHADAP HASIL BELAJAR IPA PADA MATERI PENGLIHATAN DAN ALAT OPTIK - Nurhayati Nurhayati; Nurhaty Purnama Sari (CAHAYA PENDIDIKAN, 2020)
The purpose of this research was to determine the effect of Bilingual Pocket Book toward the students’ achievement on science subject of visual sense and optical equipment at eight grade of Junior High School 50 Batam. The sampling technique that researchers use is probability sampling with cluster random sampling technique. The sample was taken by the researchers by revoking the sweepstakes conducted by the science teachers, so it was elected class VIII.B as an experimental class of 38 students and class VIII.C as a control class of 38 students. Data analysis technique was done by descriptive analysis and inferential analysis. The predetermined level of significance was = 0.05.After the researcher gave the treatment, by using the bilingual pocket book of Science in the experimental class, the average of students’ achievement on descriptive statistic of science subject in experimental class = 78. While the average of students’ achievement of science class of control = 66,10. The result of Inferential analysis from data processing hence can be known sig value. With dk = n1 + n2 - 2 = 74. t table t arithmetic then H0 is rejected and Ha is accepted. So it can be concluded that there is significant effect of bilingual pocket book toward students’ achievement on science subject at eight grade students’ of Junior High School 50 Batam